2021
DOI: 10.22541/au.161649084.48637709/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human-wildlife conflict in the roof of the world: Understanding multidimensional perspectives through a systematic review.

Abstract: Aim: Wildlife and their interaction human or human-wildlife conflict, though reported throughout human prehistory, its severity and complexity have increased in recent years. The Hindu Kush Himalaya region, rich and biodiversity and known as roof of the world have gained recognition for many conservation success but also with increasing trends of human-wildlife conflict. But, they are sparsely documented and the severity of its impacts are not known for the region. Hence, we present a systematic review on huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Acharya et al, 2017;Adedoyin et al, 2018;Akinsorotan et al, 2021;Carter & Linnell, 2016;Digun-Aweto & Van Der Merwe, 2019;Odunlami & Osumenya, 2020;Wester et al, 2019). However, a recent study showed that about 87% of HWC studies concentrated on the Asian countries (Sharma et al, 2021). This indicates a dearth of research in Africa region and other continents.…”
Section: 10 Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Acharya et al, 2017;Adedoyin et al, 2018;Akinsorotan et al, 2021;Carter & Linnell, 2016;Digun-Aweto & Van Der Merwe, 2019;Odunlami & Osumenya, 2020;Wester et al, 2019). However, a recent study showed that about 87% of HWC studies concentrated on the Asian countries (Sharma et al, 2021). This indicates a dearth of research in Africa region and other continents.…”
Section: 10 Introductionmentioning
confidence: 99%
“…While cases of HWC date back to antediluvian eras (Gordon, 2009), its severity has increased lately (Sharma et al, 2021), affecting both developed and developing nations (Lamarque et al, 2009). The developing countries are nevertheless, more vulnerable to HWC and, particularly, HWC has become more severe in Africa where majority of the people depends on agriculture, which accelerates the conversion of wildlife habitat to agricultural fields (Fairet, 2012).…”
Section: 10 Introductionmentioning
confidence: 99%
See 3 more Smart Citations